Analysis of the best types of supplements in the Fitness Exercise Program with the concept of an intelligent system as a marketing strategy effort - Virdyra Tasril, Ari Kartiko, Muhammad Mujtaba Mitra Zuana, Frans Sudirjo, Prihatin Tiyanto Priagung Hutomo (International Journal of Advanced Science and Technology, 2020)
The research objective is to utilize intelligent systems in determining the best type of supplement for fitness training programs and as an information product marketing strategy effort and can become knowledge for fitness members in consuming this type of supplement. In this case the intelligent system in question is to use one of the artificial intelligence techniques namely decision support systems in providing recommendations in the form of ranking. Sources of data obtained by observing and giving questionnaires randomly to 79 respondents. Respondents consisted of people who were doing fitness training (member fitness) and the manager of the fitness center. The method used in this research is Technique For Others Reference by Similarity to Ideal Solution (TOPSIS). As an assessment criteria in the selection of the best supplement types are Protein (C1), Efficacy (C2), Shape Type (C3) and Side Effects (C4). The alternative to the selection of supplement types is Gainer (A1), Whey (A2), Fat Burner (A3) and Creatine (A4). The results of the calculation of the TOPSIS method states that the type of Whey supplement (A2) is the best alternative solution (value 0.6914) and Gainer (A1) is the second alternative (0.457).